2001
DOI: 10.1128/cdli.8.5.1024-1027.2001
|View full text |Cite
|
Sign up to set email alerts
|

Excretory-Secretory Antigens of Trypanosoma cruzi Are Potentially Useful for Serodiagnosis of Chronic Chagas' Disease

Abstract: The reactivities of sera from chronic chagasic patients against the trypomastigote excreted-secreted antigens (TESA) of Trypanosoma cruzi strains with different biodemes were analyzed by TESA-blot and TESA–enzyme-linked immunosorbent assay (ELISA). Although both tests presented high sensitivity and specificity, TESA-ELISA is more appropriate for screening a larger number of samples

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 22 publications
1
30
0
5
Order By: Relevance
“…This assay consists of a WB prepared using exoantigens from trypomastigotes of T. cruzi strain Y, which is considered positive when a 150-kDa band appears. This method has 100% sensitivity and specificity, does not suffer cross-reactivity, permits differentiation between the acute and chronic phases of CD, and is considered a confirmatory test when conventional serological results are inconclusive (UMEZAWA et al, 1996;NAKAZAWA et al, 2001;SILVA, 2007). In the present study, anti-T. cruzi antibodies were found in 4.5% (5/111) of the analyzed canine serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…This assay consists of a WB prepared using exoantigens from trypomastigotes of T. cruzi strain Y, which is considered positive when a 150-kDa band appears. This method has 100% sensitivity and specificity, does not suffer cross-reactivity, permits differentiation between the acute and chronic phases of CD, and is considered a confirmatory test when conventional serological results are inconclusive (UMEZAWA et al, 1996;NAKAZAWA et al, 2001;SILVA, 2007). In the present study, anti-T. cruzi antibodies were found in 4.5% (5/111) of the analyzed canine serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…The TE-SA-blot showed that a 150-160 kDa band was recognised in the serum of 100% of chronic Chagas disease patients and did not react with the serum of patients with leishmaniasis (caused by organisms closely related to T. cruzi) (Umezawa et al 1996). The TESA-blot was also evaluated by Nakazawa et al (2001) using TESA from T. cruzi strains of different biodemes (WSL, Colombiana and 12SF). A 150-170 kDa polypeptide was recognised in 100% of chronic Chagas disease patients tested (with cardiac, asymptomatic, digestive and mixed forms).…”
Section: What Still Needs To Be Done Regarding Diagnosis?mentioning
confidence: 99%
“…For this reason, the ELISA format is more convenient, as it is simple, easy to perform and amenable to automation. Nakazawa et al (2001) thus developed and evaluated an ELISA using TESA-ELISA by analyzing 124 consensus samples and 204 samples of serum from individuals not infected with Chagas disease. Although the TESA-ELISA exhibited high sensitivity (100%; CI 95%: 96.3-100%) and low specificity (96%; CI 95%: 92.5-97.9%), cross-reactions were observed with cutaneous and vis-ceral leishmaniasis.…”
Section: What Still Needs To Be Done Regarding Diagnosis?mentioning
confidence: 99%
“…En este sentido cabe anotar que se obtuvieron unas pocas reacciones cruzadas con sueros de individuos con leishmaniasis visceral, lo cual ya ha sido descrito en otros estudios en los cuales se destaca que T. cruzi comparte antígenos con las diferentes especies de Leishmania spp. y T. rangeli, debido a que pertenecen a la misma familia, Trypanosomatidae (24,25,30,44). Sin embargo, el único suero con rangeliosis que se probó en este estudio no presentó reacción cruzada, que, como se sabe, hace que la especificidad de las pruebas de inmunodiagnóstico disminuya, ya que se incrementa el número de falsos positivos (45).…”
Section: Técnica De Aglutinación Directa Positivos Negativosunclassified